Effect of steam explosion on enzymatic hydrolysis and baking quality of wheat bran. (November 2017) - Aktas-Akyildiz, E.; Mattila, O.; Sozer, N.; Poutanen, K.; Koksel, H.; Nordlund, E.
Abstract: In this study, the effect of steam explosion (SE) treatment on microstructure, enzymatic hydrolysis and baking quality of wheat bran was investigated. Coarse and fine bran were treated at different steam temperatures (120–160 °C) and residence times (5 or 10 min) and then hydrolysed with carbohydrase enzymes. The SE treatment increased water extractable arabinoxylan (WEAX) content from 0.75 to 2.06% and reducing sugars from 0.92 to 2.41% for fine bran. The effect was more pronounced with increased SE temperature and residence time. The highest carbohydrate solubilisation was observed in fine bran at SE treatment of 160 °C, 5 min. WEAX content increased to 3.13% when this bran was incubated without enzyme, while WEAX content increased to 9.14% with enzyme addition. Microscopic analysis indicated that cell wall structure of wheat bran was disrupted by severe SE conditions. Supplementation of SE treated (150 °C, 10 min) bran at 20% replacement level decreased the baking quality of bread. However SE followed by enzymatic hydrolysis increased specific volume and decreased crumb hardness (on the day of baking and after three days of storage). Phytic acid content of bread supplemented with SE treated bran was lower than the one supplemented with untreated bran. Highlights: Effects of steam explosion & enzymes on carbohydrate solubility of bran was studied. High steam temperature and long residence time increased carbohydrate solubility. Steam explosion followed by enzyme treatment improved bread quality. Steam explosion followed by enzyme treatment increased fibre solubility in breads. Steam explosion decreased the phytic acid contents of breads.